Dimension-dependent toxicity of silver nanomaterials on the cladocerans Daphnia magna and Daphnia galeata. (October 2017) - Cui, Rongxue; Chae, Yooeun; An, Youn-Joo
Abstract: Silver nanomaterials (AgNMs) are widely used in many fields because of their antimicrobial properties. Depending on the shapes and dimensions of the AgNMs, their potential uses and needs vary. Consequently, vast quantities of multi-dimensional AgNMs are being manufactured and released into aquatic ecosystems, where they have toxic effects on aquatic organisms. Therefore, an assessment of the toxicities of each multi-dimensional AgNM on aquatic ecosystems is necessary. In this study, important aquatic model species, Daphnia magna and Daphnia galeata, were used to assess and compare the toxic effects of silver ions (Ag + ions) and multi-dimensional AgNMs, including silver nanoparticles (AgNPs), silver nanowires (AgNWs), and silver nanoplates (AgPLs). The results indicated that Ag + ions were more toxic than AgNMs of different dimensions and sizes, and that AgPLs were the most toxic of the AgNMs. In the case of AgNWs, the longer (20 μm) nanowire was more toxic than the shorter (10 μm) one. In addition, D. galeata was more sensitive than D. magna to both Ag + ions and AgNMs. This study elucidates the dimension-dependent toxicity of and silver ions and nanomaterials in the cladocerans D. magna and D. galeata . Further studies will be necessary to further elucidate the actual risk of multi-dimensional nanomaterials in ecosystems. Graphical abstract: Highlights: We tested the effects of silver ions and silver nanomaterials of different dimensions. Silver ions are more toxic than silver nanomaterials to Daphnia sp. Silver nanowires are the least and silver nanoplates, the most toxic to Daphnia sp. Shorter silver nanowires (10 μm) are more toxic than are longer (20 μm) ones. D. galeata is more sensitive than D. magna to silver ion and nanomaterial toxicity.